Self‐weighing and simple dietary advice for overweight and obese pregnant women to reduce obstetric complications without impact on quality of life: a randomised controlled trial. (14th February 2016) - McCarthy, EA; Walker, SP; Ugoni, A; Lappas, M; Leong, O; Shub, A
Abstract : Objective: To determine the effect of serial weighing and dietary advice compared with standard antenatal care on obstetric outcomes. Design: Randomised controlled clinical trial. Setting: Australian tertiary obstetric hospital. Population: Three hundred and eighty‐two overweight or obese non‐diabetic pregnant women at less than 20 weeks gestation with a singleton pregnancy. Methods: Women were randomised to targeted, serial self‐weighing and simple dietary advice, (intervention), or standard antenatal care (control). Main outcomes measures: The primary outcome was a reduction in a composite of obstetric complications: gestational hypertension, pre‐eclampsia, diabetes, assisted or caesarean birth, shoulder dystocia, severe perineal trauma, postpartum haemorrhage and maternal high dependency care. Secondary outcomes were gestational weight gain at 36 weeks' gestation, quality of life (QOL) and maternal serum levels of 28‐week leptin, adiponectin and C‐reactive protein (CRP). Results: There was no difference in the rate of the primary composite outcome of obstetric complications: 124/184 (67% control), 124/187 (66% intervention) [relative risk 0.98 (95% confidence interval (CI) 0.85–1.14)]. There was no difference in mean gestational weight gain [−0.9 kg (95% CI −2.0, 0.25)], QOL or leptin, adiponectin or CRP levels between intervention and control groups. Conclusions: This low‐cost, pragmatic intervention failed to prevent obstetric complications or modify maternal biochemistry or gestational weight gain in overweight or obese pregnant women. Participation in the study did not impair participants' QOL. Tweetable abstract: Serial self‐weighing and dietary advice failed to reduce obstetric complications in overweight pregnant women. Tweetable abstract: Serial self‐weighing and dietary advice failed to reduce obstetric complications in overweight pregnant women.